Incidence of different types of irritable bowel syndrome in patients with nonalcoholic fatty liver - Popović, Divna; Rošić, Stefan; Lukić, Snežana (Medicinski podmladak, 2022)
Introduction: Non-alcoholic fatty liver (NAFLD) is an excessive accumulation of fat, detected by imaging methods or histologically, in people who haven`t consumed alcohol, associated with insulin resistance and metabolic syndrome. Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder, diagnosed by Rome IV criteria, with no morphological disorders in the digestive system. Aim: Detecting frequency between different types of IBS in different degrees of steatosis to distinguish possible association between the two diseases. Material and methods: In retrospective study at the Clinic for Gastroenterohepatology of the University Clinical Center of Serbia, from January to June 2020. are diagnosed 49 patients, over 18 years, with NAFLD and IBS. Based on the ultrasound examination, patients are classified into those with I, II and III degree of steatosis, and according to the Roma IV criteria, into IBS-C, IBS-D and IBS-M type. Body Mass Index (BMI), hyperglycemia, cholesterol, triglycerides, ALT, AST, γGT, Diabetes Mellitus (DM), arterial hypertension, Gastroesophageal Reflux Disease (GERD) and cholelithiasis are examinated. Results: The total number of patients is 49, average age 52.02 ± 13.44 years, 63% women and 37% men. IBS-C and IBS-D type were more prevalent in women (69% and 91%), while IBS-M type was more common in men (75%). The frequency of IBS types according to the degree of NAFLD was not statistically significant. Highly elevated BMI, hyperglycemia, cholesterol, triglycerides, ALT, AST, γGT, DM, GERD, and cholelithiasis were predominantly present in grade II and III steatosis, while hypertension showed no statistically significant difference. Highest prevalence, in patients with elevated cholesterol, was in IBS-C type (77%). Conclusion: Patients with NAFLD and IBS are predominantly female. NAFLD is associated with metabolic syndrome, insulin resistance, GERD, and cholelithiasis. No association was shown between the degree of steatosis and the type of IBS, except in cholesterol, with the highest frequency in grade III of steatosis and the IBS-C type.